Hubungan Tingkat Pengetahuan dengan Sikap Pedagang terhadap Pencegahan Penularan Covid-19 di Pasar Gandrungmangu Cilacap - Muhammad Mufti Dewantara; Mia Kusmiati; Rizki Perdana (Bandung Conference Series: Medical Science, 2022)
Abstract. Coronavirus disease 2019 (Covid-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is a major global health problem at the moment. The transmission of Covid-19 occurs through human-to-human, so prevention efforts are needed to suppress the spread, such as wearing masks, washing hands, and maintaining distance. Individual knowledge about preventing Covid-19 transmission is the basis for determining attitude in an effort to prevent transmission. The research was conducted in the market because the market is a crowded place so traders are at risk of contracting Covid-19. This study aims to analyze the relationship between the level of knowledge and attitudes of traders towards the prevention of Covid-19 transmission at the Gandrungmangu Market, Cilacap. This research is an analytic cross sectional study using primary data obtained from filling out questionnaires by 108 respondents. Samples were taken using purposive sampling technique. The statistical analysis using Fisher’s Exact test with p<0.05 was considered significant. The results of this study indicate that the majority of respondents have a good level of knowledge (59.3%) and good attitudes (75,9%). This study also describes that there is a significant relationship between the level of knowledge and attitudes towards preventing Covid-19 transmission (p=0.000). So, it can be concluded that the better the level of knowledge, the better the attitudes shown. Abstrak. Coronavirus disease 2019 (Covid-19) merupakan penyakit infeksi yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) dan menjadi masalah utama kesehatan global saat ini. Penularan Covid-19 terjadi secara human-to-human transmission, sehingga upaya pencegahan sangat diperlukan dalam menekan penyebaran seperti memakai masker, mencuci tangan, dan menjaga jarak. Pengetahuan individu tentang pencegahan penularan Covid-19 merupakan dasar penentuan sikap dalam upaya pencegahan penularan. Penelitian dilakukan di pasar karena pasar merupakan tempat yang ramai sehingga pedagang berisiko tertular Covid-19. Penelitian ini bertujuan untuk menganalisis hubungan tingkat pengetahuan dengan sikap pedagang terhadap pencegahan penularan Covid-19 di Pasar Gandrungmangu Cilacap. Penelitian ini merupakan penelitian analitik cross sectional dengan menggunakan data primer yang diperoleh dari pengisian kuesioner oleh 108 responden. Sampel diambil menggunakan teknik purposive sampling. Analisis statistik pada penelitian ini menggunakan uji Fisher’s Exact dengan p<0,05 dianggap signifikan. Hasil penelitian menunjukkan bahwa mayoritas responden memiliki tingkat pengetahuan baik (59,3%) dan sikap baik (75,9%). Penelitian ini juga menggambarkan adanya hubungan yang signifikan antara tingkat pengetahuan dan sikap terhadap pencegahan penularan Covid-19 (p=0,000). Sehingga dapat disimpulkan bahwa semakin baik tingkat pengetahuan maka sikap yang ditunjukkan juga semakin baik.